2016
DOI: 10.1021/acs.inorgchem.6b01646
|View full text |Cite
|
Sign up to set email alerts
|

Cu(I) Complexes of Pincer Pyridine-Based N-Heterocyclic Carbenes with Small Wingtip Substituents: Synthesis and Structural and Spectroscopic Studies

Abstract: Six new Cu(I) complexes with pincer N-heterocyclic carbene (NHC) ligands of the type 2,6-bis(3-alkylimidazol-2-ylidene)pyridine, I(R), and 2,6-bis(3-alkylimidazol-2-ylidene)methylpyridine, I(R), where R = Me, Et, and Pr have been synthesized using Cu precursors and bis(imidazolium) salts. All of these compounds, namely, [Cu(IMe)](PF), 1; [Cu(IEt)](PF), 2; [Cu(IPr)](PF), 3; [Cu(IMe)](PF), 4; [Cu(IEt)](PF), 5; and [Cu(IPr)](PF), 6, have been characterized by H andC NMR spectroscopies, elemental analysis, solutio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 54 publications
0
26
1
Order By: Relevance
“…Domyati et al reported on copper(I) complexes with pincer N ‐heterocyclic carbene (NHC) ligands starting from the reaction of [Cu(MeCN) 4 ]PF 6 or [Cu(MeCN) 4 ]SbF 6 and an in situ generated NHC at room temperature in the absence of air and moisture . Consequently, other tetrakis(acetonitrile) copper(I) complexes with varying anions are known, which might serve as starting materials for simple metathesis reaction to obtain [Cu(MeCN) 4 ]IO 4 .…”
Section: Resultsmentioning
confidence: 99%
“…Domyati et al reported on copper(I) complexes with pincer N ‐heterocyclic carbene (NHC) ligands starting from the reaction of [Cu(MeCN) 4 ]PF 6 or [Cu(MeCN) 4 ]SbF 6 and an in situ generated NHC at room temperature in the absence of air and moisture . Consequently, other tetrakis(acetonitrile) copper(I) complexes with varying anions are known, which might serve as starting materials for simple metathesis reaction to obtain [Cu(MeCN) 4 ]IO 4 .…”
Section: Resultsmentioning
confidence: 99%
“…When the coordination geometry of the metal center is different, for example octahedral as for Fe 2+ ( 6 bii ) or linear as for Ag + ( 6 biv ), molecular species containing two NHC ligands are obtained (see also the Supporting Information, Figure S5). Similar coordination modes were also found in the literature for conventional, non‐amphiphilic ligands …”
Section: Methodsmentioning
confidence: 99%
“…Similarc oordination modes werea lso found in the literature for conventional, non-amphiphilic ligands. [20] The self-assembly behavior of the new,h ybrid surfactants 6a,bi was investigated next. We learnedf rom SAXS measurements (Figure 1e)t hat the presence of the metal has am arked effect on the structure of the LC phases.…”
mentioning
confidence: 99%
“…In all species, the nitrogen atoms of the pyridine are directed towards the metal centers and their distances, ranging from 2.4220(18) Å to 2.8298(18) Å, reveal a weak interaction between these two atoms. Recently, Tahsini and co-workers demonstrated that the formation of this type of dinuclear complexes is only possible when the NHCs are directly bound to the pyridine ring, whereas mononuclear complexes are formed when a methylene spacer between the two moieties is present [67]. Reddy and co-workers further extended this family of complexes by reporting carbaphosphazene derivatives (Scheme 33) [68].…”
Section: Pyridine Bridge (Cnc Ligands)mentioning
confidence: 99%